2023
DOI: 10.1039/d3ra01965a
|View full text |Cite|
|
Sign up to set email alerts
|

A novel, efficient and magnetically recyclable Cu–Ni bimetallic alloy nanoparticle as a highly active bifunctional catalyst for Pd-free Sonogashira and C–N cross-coupling reactions: a combined theoretical and experimental study

Abstract: In this study, a Fe3O4@SiO2@Cyt-Ni/Cu nanocomposite as a novel heterogeneous bimetallic catalyst was synthesized which exhibits efficient performance for the Sonogashira and C–N cross-coupling reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Compared with monometallic MOFs, bimetallic MOFs exhibit better performance in organic catalysis. [21][22][23] In particular, MOFcatalyzed oxidative amidation reactions have been sustained over the past few years. However, these research only reported the use of single-metal catalysts, such as Ni-MOFs [24] and Cu-MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with monometallic MOFs, bimetallic MOFs exhibit better performance in organic catalysis. [21][22][23] In particular, MOFcatalyzed oxidative amidation reactions have been sustained over the past few years. However, these research only reported the use of single-metal catalysts, such as Ni-MOFs [24] and Cu-MOFs.…”
Section: Introductionmentioning
confidence: 99%